Spanish across domains in the United States : education, public space, and social media - Salgado-Robles, Francisco; Lamboy, Edwin M., 1967- (Brill's studies in language, cognition and culture ;, 2020)
"This edited volume adopts a new angle on the study of Spanish in the United States, one that transcends the use of Spanish as an ethnic language and explores it as a language spreading across new domains: education, public spaces, and social media. It aims to position Spanish in the United States in the wider frame of global multilingualism and in line with new perspectives of analysis such as superdiversity, translanguaging, indexicality, and multimodality. All the 15 chapters analyze Spanish use as an instance of social change in the sense that monolingual cultural reproduction changes and produces cultural transformation. Furthermore, these chapters represent five macro-regions of the United States: the Southwest, the West, the Midwest, the Northeast, and the Southeast"--